Nora Hämäläinen. Literature and Moral Theory. Bloomsbury, 2016. - Anthony M Dotterman (Studies in 20th & 21st Century Literature, 2019)
Review of Nora Hämäläinen. Literature and Moral Theory. Bloomsbury, 2016.
Keywords: Book Review; Nora Hämäläinen; Literature and Moral Theory